Sustainable use and conservation of Vitex doniana Sweet: unlocking the propagation ability using stem cuttings - Achigan-Dako, Enoch G.; N'Danikou, Sognigbe; Tchokponhoue, A.D.; Assogba-Komlan, F.; Larwanou L.; Vodouhe S.R.; Ahanchédé, A. (Istituto Agronomico per l'Oltremare (Italy), 2014)
One of the major constraints for domesticating widely used wild tree resources by local communities is the lack of adequate propagation techniques. In the case of Vitex doniana, seed propagation has usually been reported difficult and vegetative regeneration is rarely explored. To understand how stem cutting size or hormone application affect the regeneration and early growth ability in that species we used two categories of cutting diameter (1cmVitex doniana to reduce the pressure on wild tree population in Benin.